Coupling hydrodynamics with comoving frame radiative transfer: III. the wind regime of early-type B hypergiants - Bernini Peron, Matheus; Sander, Andreas A. C.; Najarro, F.; Sabhahit, G. N.; Pauli, D.; Lefever, Roel; Vink, J. S.; Ramachandran, Varsha; Oskinova, L. M.; González i Torà, Gemma; Schösser, Elisa C. (Astronomy and astrophysics, 2025)
Methods. Using the stellar atmosphere code PoWRHD, we calculated the first hydrodynamically consistent atmosphere model in the BHG wind regime. These models inherently connect stellar and wind properties in a self-consistent way. They also provide insights into the radiative driving of the calculated wind regimes and enable us to study the influence of clumping and X-rays on the resulting wind properties and structure. - Results. Our hydrodynamically consistent atmosphere model nicely reproduces the main spectral features of ζ1 Sco and represents a new framework of quantitative spectroscopy. The obtained mass-loss rate is higher than for BSGs of similar spectral types. However, despite the spectral morphology, the wind optical depth of BHG atmospheres is still considerably below unity, making them less of a transition type than the Of/WNh stars. To reproduce the spectrum, we need mild clumping with subsonic onset ( f∞ = 0.66, cl = 5 km s−1). The wind shows a shallow-gradient velocity profile that deviates from the widely used β law. Even beneath the critical point, the wind is mainly driven by Fe III opacity. - Conclusions. Our investigation suggests that despite more mass loss, early-type Galactic BHGs have winds that are relatively similar to late-type BSGs. Their winds are not sufficiently optically thick that we would characterize them as “transition-type” stars, unlike Of/WNh, implying that emission features arise more easily in cooler than in hotter stars. The spectral BHG appearance is likely connected to atmospheric inhomogeneities already arising beneath the sonic point. To reach a spectral appearance similar to known LBVs, BHGs need to be either closer to the Eddington limit or have higher wind clumping than inferred for ζ1 Sco.
Gesehen am 06.10.2025